1984
DOI: 10.1002/apmc.1984.051220111
|View full text |Cite
|
Sign up to set email alerts
|

Etude calorimétrique de la rétention de l'eau par les résines novolaques

Abstract: Moisture retention in various substituted novolake resins has been investigated by differential scanning calorimetric analysis. Water molecules leave the polymer network in a two step drying process. The first one occurs at T < Tg, the second at T > T, and requires an external energy supply. The energy recorded in the second drying step indicates the presence of a dipolar link. ZUSAMMENFASSUNG:In verschiedenen Novolaken wurde der Feuchtigkeitsgehalt durch Differentialkalorimetrie bestimmt. Wassermolekule verla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1985
1985
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…10) a constant decrease in thickness and hence a continuous loss in weight. Starting with freshly spin-coated resist, it can be shown that the soft bake at 95~ provides a 16% weight loss due to water (16) and solvent evaporation. Increasing temperature up to 200~ shows an additional weight loss of 15% due to residual solvent evaporation and oligomer vaporization (17).…”
Section: Effect Of Weigl~t Loss On Planarization Resultsmentioning
confidence: 99%
“…10) a constant decrease in thickness and hence a continuous loss in weight. Starting with freshly spin-coated resist, it can be shown that the soft bake at 95~ provides a 16% weight loss due to water (16) and solvent evaporation. Increasing temperature up to 200~ shows an additional weight loss of 15% due to residual solvent evaporation and oligomer vaporization (17).…”
Section: Effect Of Weigl~t Loss On Planarization Resultsmentioning
confidence: 99%
“…An effect was observed for the delay between softbake and exposure (Hia) which was unexpected in its magnitude. However, it is believed to be an artefact of the short first level setting employed (5 mm): apparently, insufficient time ( <60 see) was allowed for the water concentration in the wafer to equilibrate with the atmosphere before introducing it into the high vacuum of the exposure chamber [10]. exposed sequentially, such as in an X-ray stepper, the differences in reaction time may require substantially longer holding times of up to 1 h in order to allow the fields exposed last to "catch up" .…”
Section: Identification Of Critical Parametersmentioning
confidence: 99%
“…Courbe exptrimentale de thermogravimttrie de la variation de masse Q ( t ) d'un photoresist HPR 204, dtpost sur de l'aluminium, au cours du temps, A une temptrature de 70°C et exploitation de cette courbe pour dtterminer la valeur du coefficient de diffusion D selon Eq (3). …”
unclassified